A Case of Herpes Simplex Virus-1 Encephalitis from a Medicolegal Point of View. (10th June 2018) - Feola, Alessandro; Mancuso, Anna; Arcangeli, Mauro
Abstract : We present a case of herpes simplex virus-1 encephalitis (HSVE) and discuss the difficulty of early diagnosis and the possibility of a wrong or delayed diagnosis and treatment of this encephalitis. We show the importance of considering HSVE to pursue every case of suspicious medical liability.